The Effect Of Marketing Mix, Brand Image and Service Quality On Customer Loyalty In Bank BNI Syariah - Ade Sofyan Mulazid; yunia silvia sesunan; Ligar Fadilah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Theobjectiveofresearchwas to findouttheeffectof marketing mix, brand image, and service quality on customer loyalty in Fatmawati Branch of Bank BNI Syariah. Data employed in this research was primary one; data collection was carried out using questionnaire distributed directly with random sampling method; the object of research was customers of Bank BNI Syariah. This research was expected to contribute to the bank, particularly Fatmawati Branch of Bank BNI Syariah, in order to give good service to their customers. The result of research showed that marketing mix, brand image, and service quality affected positively and significantly the customer loyalty in Fatmawati Branch of Bank BNI Syariah either partially or simultaneously.